Challenges Faced By Bookshops in the City of Kampala : studies of fresh vine bookshop and the uganda bookshop - Namitala Diana Kisakye (Mukono UCU, 2010)
Descriptive Cataloguing Uganda Christian University BLIS
Includes references and appendix
Keywords: Challenges of Bookshops